AUTONOMOUS LEARNING IN GRADUATE ENGLISH EDUCATION: INSIGHTS FROM INDONESIA AND THAILAND - Nurul Evita Istiqomah; Fazri Nur Yusuf (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
Autonomous learning is widely recognized as essential for graduate students, empowering them to take responsibility for their learning. However, practical understanding of how autonomous learning is sustained in higher education contexts remains limited, particularly at the graduate level. This study explored autonomous learning among graduate students enrolled in English language education programs in Indonesia and Thailand. The study involved 25 graduate students, comprising 17 students from Indonesia and 8 students from Thailand. Data were collected using an adapted Autonomous Learning Scale (ALS) and open-ended questions to examine students’ learning experiences, strategies, and challenges. Questionnaire data were analyzed using descriptive statistics, while qualitative responses underwent thematic analysis. The findings revealed relatively moderate levels of autonomous learning, with an overall mean score of 3.11, indicating developing responsibility, learning independence, and intrinsic motivation. However, challenges persisted in learning habits, particularly in time management and overcoming procrastination. Students also adopted diverse learning strategies, including utilizing digital resources, participating in peer discussions, and engaging in self-directed learning practices. The findings suggest that learner autonomy should be understood as a dynamic and continuously developing process requiring not only cognitive independence but also sustained behavioral regulation and motivational consistency in higher education contexts. This study enriches scholarship on learner autonomy by offering cross-contextual insights and underscoring the importance of sustained development in higher education.